Differential specific mechanical energy as a quality parameter in racing alpine skiing - Supej, M. (Journal of Applied Biomechanics, 2008)
An important question in alpine skiing is how to determine characteristics of well-performed ski turns, an issue that has become more crucial with the arrival of new carving skis. This article introduces a new method for estimating the quality of skiing at each point of observation based on mechanical energy behavior that can be measured using established motion analysis techniques. It can be used for single or multiple-skier analyses for evaluation of skiing technique as well as racing tactics. An illustration of its use is shown by analyzing 16 top-level racers using a 3-D kinematical system and video recorded during an alpine ski world cup race. Based on energy behavior of several racers, it is demonstrated that the most direct line with shortest radius of turn is not necessarily the most effective strategy in contrast to what some coaches believe.